Effect of Heterogeneity on Recovery Factor for Carbonate Reservoirs. A Case Study for Mishrif Formation in West Qurna Oilfield, Southern Iraq - Al-Dujaili, Ahmed N.; Shabani, Mehdi; S. AL-Jawad, Mohammed (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Oil recovery could be impacted by the relation between vertical permeability (Kv) and horizontal permeability (Kh) (Kv/Kh). 4816 plugs that have been getting hold of 18 wells of Mishrif formation in the West Qurna oilfield were used. Kv/Kh data provided some scatter, but the mean is ~1. Kv/Kh =1 was used for the Petrel model before upscaling according to the heterogeneity of each layer.Kv/Kh values for Mishrif Formation in West Qurna Oilfield are 0.8 for relatively homogeneous, 0.4 for heterogeneous rock, and 0.1 for cap rocks (CRII).   Eclipse TM was used for reservoir simulation. PVT and SCAL data enhanced the simulation process.  The results showed that the reduction of Kv/Kh to 0.9 for the mA unit would reduce the recovery factor (RF) by ~0.9% and continuing lowering would reduce RF more, while the same reduction would reduce RF by ~1% in the mB1 unit. The reduction would be 0.8, which increases RF by ~0.5% for the mB2U unit, while there was no effect on RF in the CRII unit whatever the reductions.